The real MCTS/MCITP Exam 70-648 : upgrading your MCSA on Windows server 2003 to Windows server 2008 ; prep kit - Posey, Brien; Azad, Tariq (Syngress ; Elsevier Science [distributor], 2008)
This exam is designed to validate Windows Server 2003 Microsoft Certified Systems Administrators (MCSAs) AD and Application Platform Technical Specialists skills. The object of this exam is to validate only the skills that are are different from the existing MCSA skills. This exam will fulfill the Windows Server 2008 Technology Specialist requirements of Exams 70-640 and 70-643. The Microsoft Certified Technology Specialist (MCTS) on Windows Server 2008 credential is intended for information technology (IT) professionals who work in the complex computing environment of medium to large c.